Evolution and Geological Significance of Larger Benthic Foraminifera Second Edition - K. BouDagher-Fadel, Marcelle (UCL Press, 2018)
Evolution and Geological Significance of Larger Benthic Foraminifera is a unique, comprehensive reference work on the larger benthic foraminifera. This second edition is substantially revised, including extensive re-analysis of the most recent work on Cenozoic forms. It provides documentation of the biostratigraphic ranges and paleoecological significance of the larger foraminifera, which is essential for understanding many major oil-bearing sedimentary basins. In addition, it offers a palaeogeographic interpretation of the shallow marine late Paleozoic to Cenozoic world. Marcelle K. BouDagher-Fadel collects and significantly adds to the information already published on the larger benthic foraminifera. New research in the Far East, the Middle East, South Africa, Tibet and the Americas has provided fresh insights into the evolution and palaeographic significance of these vital reef-forming forms. With the aid of new and precise biostratigraphic dating, she presents revised phylogenies and ranges of the larger foraminifera. The book is illustrated throughout, with examples of different families and groups at the generic levels. Key species are discussed and their biostratigraphic ranges are depicted in comparative charts, which can be found at